The impact of a brief structured intervention on young offenders masculine identity: a mixed methods study. Issue 3 (6th August 2018) - Blagden, Nicholas; Perrin, Christian
Abstract : Purpose: Masculinity in young men can be considered a dynamic risk factor. However, there is a lack of interventions designed to support men and young men to explore the ways in which the concept of masculinity contributes to shaping their individual identity. The purpose of this paper is to explore young offenders' perceptions of a programme designed to address masculinity and criminogenic attitudes and evaluate whether the programme contributed to any personal change/development and what core learning they took from the course. Design/methodology/approach: The research utilised a mixed-methods approach to address aims and objectives. Findings: The quantitative results found that there was a pre-/post-course reduction in toughness and increase in self-esteem and risk-taking perceptions. The qualitative results identified four superordinate themes reconstruing masculine self-realisation awareness and reflection group dynamics and course relationships and unintended consequences. The course-assisted participants in helping to reconstrue aspects of being a man made them think about the future and allowed for participants to consider their possible and desired selves. Research limitations/implications: The research has policy and practice implications for brief interventions targeted at young offenders. Originality/value: The research evaluates a novel intervention aimed at addressing young offenders masculine beliefs and identities. The research has implications for working with this client group.